Research hotspots and emerging trends of mesenchymal stem cells in cardiovascular diseases: a bibliometric-based visual analysis - Jiang, Zhihang; Yu, Jiajing; Zhou, Houle; Feng, Jiaming; Xu, Zehui; Wan, Melisandre; Zhang, Weiwei; He, Yuqing; Jia, Chengyao; Shao, Shuijin; Guo, Haidong; Liu, Baonian (Frontiers in Cardiovascular Medicine, 2024)
Background Mesenchymal stem cells (MSCs) have important research value and broad application prospects in cardiovascular diseases (CVDs). However, few bibliometric analyses on MSCs in cardiovascular diseases are available. This study aims to provide a thorough review of the cooperation and influence of countries, institutions, authors, and journals in the field of MSCs in cardiovascular diseases, with the provision of discoveries in the latest progress, evolution paths, frontier research hotspots, and future research trends in the regarding field. Methods The articles related to MSCs in cardiovascular diseases were retrieved from the Web of Science. The bibliometric study was performed by CiteSpace and VOSviewer, and the knowledge map was generated based on data obtained from retrieved articles. Results In our study, a total of 4,852 publications launched before August 31, 2023 were accessed through the Web of Science Core Collection (WoSCC) database via our searching strategy. Significant fluctuations in global publications were observed in the field of MSCs in CVDs. China emerged as the nation with the largest number of publications, yet a shortage of high-quality articles was noted. The interplay among countries, institutions, journals and authors is visually represented in the enclosed figures. Importantly, current research trends and hotspots are elucidated. Cluster analysis on references has highlighted the considerable interest in exosomes, extracellular vesicles, and microvesicles. Besides, keywords analysis revealed a strong emphasis on myocardial infarction, therapy, and transplantation. Treatment methods-related keywords were prominent, while keywords associated with extracellular vesicles gathered significant attention from the long-term perspective. Conclusion MSCs in CVDs have become a topic of active research interest, showcasing its latent value and potential. By summarizing the latest progress, identifying the research hotspots, and discussing the future trends in the advancement of MSCs in CVDs, we aim to offer valuable insights for considering research prospects.